Compreendendo o Ser da pessoa com câncer: suas posturas e possibilidades existenciais - SIQUEIRA, Karina Machado (2006)
In despite of important advances that occurred in the last years referring to diagnosis and treatment of cancer this disease has proved to be one of the main causes of death in the world affecting a significant part of the population The expressive number of people in health care institutions for cancer treatment leads us to assume a reflective attitude in relation to the way it is being treated by health care professionals The purpose of the development of this research was to unveil the meaning of being-with-cancer for oncologic patients trying to understand them in this experience and trying to find new ways to take care of these people Based on the insight that only people who have actually gone through the experience of suffering from cancer are able to transmit the meaning and the importance of what they have been experiencing I opted for the methodology of qualitative research phenomenological modality based on the philosophical reference of Edmund Husserl Phenomenology according to Husserl is a tour through the world of experiences having as its objective to unveil the essences inherent to the phenomenon Interviews were conducted with eleven patients interned in a health care institution specialized in cancer treatment located in Goiânia GO All the patients were adults and aware of the diagnosis I adopted some ideas of Martin Heidegger s existencial ontology to better develop data analysis I could learn that cancer shows itself to the Being who lives this situation as a difficult experience saturated with suffering and pain Receiving the diagnosis revealed itself as one of the worst moments for the patient as an experience among other feelings the anguish of the unknown and fear of death Approaching the world of these people s lives I noticed how much cancer as a reality in the being s life can affect both their self-perception and behaviour as well as their social relations From the moment on in which the Being is confronted with the reality of living with a severe disease several existencial projects tend to be cancelled or modified Besides the countless sufferings provoked by the disease the stigma that envolves cancer is responsable for the maintenance of prejudice which increase the suffering and wear out the sick person Being confronted with the necessity of living with a severe health problem people in many cases search ways of facing this which differ from the ways offered by conventional medicine; among these stand out the practices based on popular knowledge and religiosity The trust in divine power emerged in a significant way in the patients discourse as a way of strengthening and overcoming The presence of significant people such as relatives and friends were considered important by those who experienced being sick To unveil the meaning of living with cancer allowed me a comprehension of what the person was experiencing signalling the need for discussing feelings and sharing his/her pains sadness and worries Taking care of these people implies developing the sensibility of seeing the Being as someone given the gift of awareness of the situation he finds himself in and as someone who needs care directed to his singularity